Restricting calf presence without suckling shortens postpartum interval to first ovulation - Hoffman, D.P.; Stevenson, Jeffrey S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
The suckling interaction between a cow and her calf is one of the factors that maintains a cow in postpartum anestrus (the period between calving and the beginning of first estrous cycle). Anestrus continues if the cow perceives that her calf is attempting to nurse, even when the mammary glands have been denervated or removed. Cross-fostering of an alien calf to a cow fails to maintain postpartum anestrus, indicating that cow-calf recognition is also a factor. We restricted calves so they could nuzzle the cow's head and neck but could not suckle. Compared with weaning calves 1 wk postpartum, restriction lengthened the interval to first postpartum ovulation but less than with normal suckling. These results suggest that maintaining cow-calf recognition in the absence of the suckling stimulus is an essential part of the nursing mechanism that prolongs anovulation. Thus, blocking the cow's recognition of her calf might further decrease the postpartum interval to first ovulation.
Keywords: Beef; Suckling; Anestrus; Estrous cycles; Postpartum